Do Foreign Direct Investments Promote Employment in GCC Countries? - Alenezi, Hamood; zmami, Mourad; Khan, Sania; Bahudhailah, Mohammad; Almutiri, Abdullah Shwaish (Journal of Ecohumanism, 2024)
The impact of foreign direct investments on the labor market has attracted a lot of attention on behalf of academics. This this study contributes to the literature by analyzing the short-run and long-run impacts of FDI on employment in GCC countries during the period 1990 and 2019. To do that, we used the PMG-ARDL model, which allows accounting for cross-section dependence. The analysis shows that GDP, capital stock, international trade and FDI have a positive effect on employment in the long-run. More specifically, an increase in FDI flows by 1% induces a rise in employment by 0.194% in the long-run. The results of the empirical analysis also show that FDI has no significant effects on employment in the short-run. In addition, GDP positively influences employment, whereas international trade has a detrimental effect. Finally, the short-run country-specific analysis suggests that FDI flows increase employment in Bahrain and Qatar in the short-run while it reduces it in Kuwait, Oman, Saudi Arabia, and the United Arab Emirates. Foreign Direct Investments